2022
DOI: 10.1136/bmjgh-2021-006872
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing quality midwifery care in humanitarian and fragile settings: a systematic review of interventions, support systems and enabling environments

Abstract: IntroductionWomen and children bear a substantial burden of the impact of conflict and instability. The number of people living in humanitarian and fragile settings (HFS) has increased significantly over the last decade. The provision of essential maternal and newborn healthcare by midwives is crucial everywhere, especially in HFS. There is limited knowledge about the interventions, support systems and enabling environments that enhance midwifery care in these settings. The aim of this paper is to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 49 publications
1
7
0
2
Order By: Relevance
“…Staff shortage has existed for many decades and harms the quality of care. Miseda et al (29) concur with the study's ndings and indicate that the shortage of healthcare workers has signi cantly restrained the realisation of healthassociated Millennium Development Goals (MDG). A shortage of midwives is a severe obstacle to providing quality maternal and child health services (30).…”
Section: Themes and Sub-themessupporting
confidence: 56%
“…Staff shortage has existed for many decades and harms the quality of care. Miseda et al (29) concur with the study's ndings and indicate that the shortage of healthcare workers has signi cantly restrained the realisation of healthassociated Millennium Development Goals (MDG). A shortage of midwives is a severe obstacle to providing quality maternal and child health services (30).…”
Section: Themes and Sub-themessupporting
confidence: 56%
“…Globally, research has shown that midwives are not yet adequately utilized in humanitarian crises; therefore, guidelines and strategies are urgently needed to incorporate the scope of midwifery practice in providing essential and lifesaving SRHR services 23,24 . In the aftermath of severe flooding in Bangladesh, this project demonstrated a successful SRHR service delivery mechanism through deploying midwives in the rural health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, research has shown that midwives are not yet adequately utilized in humanitarian crises; therefore, guidelines and strategies are urgently needed to incorporate the scope of midwifery practice in providing essential and lifesaving SRHR services. 23,24 In the aftermath of severe flooding in Bangladesh, this project demonstrated a successful SRHR service delivery mechanism through deploying midwives in the rural health facilities. It demonstrated how health systems can be made resilient to climate-induced natural disasters by the systematic deployment of midwives to the lowest-tier health centers closest to the communities, allowing them to champion and safeguard uninterrupted SRHR for women and girls.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…Providing midwives with refresher training and opportunities for clinical simulation of emergencies and rare cases can be an effective technique to enhance skill performance ( 22 ). Moreover, supportive supervision of midwives also plays a pivotal role in improving the quality of care ( 23 ). One study with village midwives in Sudan found that consistent and sufficient supervision in conjunction with follow-up improved their skills and knowledge ( 24 ).…”
Section: Discussionmentioning
confidence: 99%